0786 ADHD Symptoms Moderate the Neural Vulnerability of Inhibition to Sleep Loss in Children. (12th April 2019) - Saletin, Jared M; Queiroz Campos, Gabriela de; Haddad, Jessica; Carskadon, Mary A; Dickstein, Daniel P
Abstract: Introduction: Sleep disruption is a proposed mechanism underlying disinhibition in attention-deficit/hyperactivity-disorder (ADHD); however, whether ADHD symptoms bestow increased vulnerability to sleep loss is unknown. Thus, we combined a behavioral go/no-go paradigm with functional neuroimaging in a dimensional sample of child ADHD to test whether those with more ADHD symptoms will be less resilient to the consequences of short sleep. Methods: 13 children (7F; aged 11.7±1.3 years) were characterized for ADHD symptomatology (inattention and hyperactivity/impulsivity) using Conners-3 scales, before sleeping at home for a week (9.5h time-in-bed [TIB]). Each then slept in the laboratory for two consecutive EEG-monitored nights: baseline (9.5h TIB) followed by restriction to 4h TIB (20h extended wake). fMRI-monitored visual go/no-go task assessing the neural systems underlying behavioral inhibition occurred each morning. Mixed-effects modelling assessed whether ADHD symptoms moderate the impact of sleep loss on behavioral and neural indices of inhibition; all models covaried age and gender. Results: Our sample captured a range of parent-rated ADHD symptoms (inattention T -scores: 38-72; mean: 51.15±10.38; hyperactivity/impulsivity: 41-89; mean: 54.7±14.2). Extended wakefulness was associated with faster (213.5 ms) response times (RT) on go/no-go trials after commission errors ( F (1, 10.06)=10.46; p <.009). This effect was moderated by inattention ( b =3.65; t =2.89; p =.016); that is, error-dependent RT changes were present only for children with few symptoms. Consistent with an increased failure to integrate error into behavior, symptoms (here, hyperactivity/impulsivity) were also associated with greater decreases in fMRI activation after sleep loss: activity associated with making commission errors in the right insula and activity associated with successful inhibition in the dorsal anterior cingulate cortex (voxel-wise p <.005; k =20mm 3 ). Conclusion: These data indicate that a short acute dose of partial sleep loss by extending wakefulness 5.5 hours can disrupt inhibition in children. ADHD symptoms were associated with differential sleep restriction changes in both behavioral and neural indices of inhibition. While preliminary, these results support the hypothesis that ADHD symptoms may bestow increased vulnerability to sleep loss in youth, thus underscoring the importance of supporting healthy sleep in children with this disorder. Support (If Any): K01MH109854 (JMS)